Perbandingan Keamanan Transaksi Seluler Menggunakan NFC dan Kode QR - Lucia Nugraheni Harnaningrum; Kristoforus Nanda Mahardhian (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
Mobile device transactions have become commonplace today. Quick-response (QR) codes and near-field communication (NFC) are popular cashless and contactless payment methods. These two payments have their characteristics. NFC payments use secure elements that encrypt credential data to ensure safe transactions. In contrast, QR code payments transmit data in its original form without encryption. Existing data are sent between devices in the form of original data. Given the extensive adoption of these methods, it is imperative to secure transaction data to prevent theft and misuse. It is necessary to know and compare the security level of each transaction and provide the best recommendations. This study undertook a comparative analysis of the security and performance of NFC and QR code-based mobile payment models. The study found that NFC transactions required 1,074 ms for encryption, while QR code transactions took 5.9359 ms. The entropy value, indicating data randomness, was 3.96 for NFC and 3.23 for QR codes. The P value, representing statistical significance, was 0.45 for NFC and 0.069 for QR codes. Both payment methods demonstrated acceptable levels of safety, with processing times and data randomness within satisfactory ranges. However, the analysis concludes that NFC transactions offer superior performance in terms of processing time and data security compared to QR code transactions.